Sarcomas with sclerotic epithelioid phenotype harboring novel EWSR1‐SSX1 fusions. Issue 9 (18th May 2021) - Antonescu, Cristina R.; Rosenberg, Andrew E.; Xie, Ziyu; Zhang, Lei; Perell, Katharina Anne; Loya, Anand C.
Abstract: Undifferentiated sarcomas remain difficult to classify. Despite the remarkable advances in sarcoma classification made by the increased application of RNA sequencing in clinical practice, the unexpected result of a novel gene fusion raises further questions regarding the tumor histogenesis and subclassification. In this study, we present two high grade sarcomas with epithelioid phenotype occurring in the deep‐soft tissues (shoulder, thigh) of young adults which based on the non‐specific pathologic findings were deemed unclassified and subjected to targeted RNA sequencing for further diagnostic interpretation. The results showed an identical EWSR1 exon 7‐ SSX1 exon 5 fusion. The breakpoints in both genes represent similar hot spots as seen in Ewing sarcoma and synovial sarcoma, generating a fusion transcript predicted to be in frame, and to retain the same protein domains within the fusion oncoprotein. These results were further confirmed by FISH analysis for both break‐apart and fusion come‐together assays in both genes. Both tumors showed a round to epithelioid morphology associated with extensive stromal hyalinization and necrosis. One case showed scattered psammomatous calcifications. The tumors shared a similar immunoprofile, including reactivity for EMA, CK, TLE1, BCOR, and CD99, while negative for S100, SOX10, CD34, SMA, and desmin. Both cases showed MUC4 positivity (one diffuse, one patchy), while one case showed patchy ALK positivity. One patient developed lymph node metastases, while the other showed no evidence of disease at 6‐month follow‐up. Neither case fit in any known pathologic categories. Larger series are needed to interrogate if the presence of EWSR1‐SSX1 fusion defines a novel pathologic entity of a sarcoma with epithelioid cytomorphology, sclerotic stroma, and epithelial differentiation immunohistochemically.